CT PERFUSION IN ONCOLOGICAL IMAGING - Djuric-Stefanovic, Aleksandra; Mitrovic Jovanovic, Milica; Kovac, Jekena; Ivanovic, Aleksandar; Ostojic, Slavenko; Grubor, Nikica; Stojakov, Dejan; Sabljak, Predrag (Medical Research, 2026)
Computed tomography (CT) perfusion is CT examination modality that enables visualization and non-invasive quantitative assessment of tissue perfusion.  Application of CT perfusion in oncology enables non-invasive detection and quantification of neo-angiogenesis (i. e. pathological vascularization) of various malignant tumors. Based on value of CT perfusion parameters, it is possible to distinguish neoplasm from healthy tissue, malignant from benign tumors, high-aggressive from low-aggressive tumors, and good from poor tumor response to oncological therapy. Basic principle of performing the low-dose CT perfusion implies repeated scanning of selected region where tumor is located, using reduced tube voltage and current, in short time intervals after intravenous administration of small bolus of iodine contrast by automatic injector with a high flow rate. Using different kinetic-mathematical models, several software for CT perfusion analysis have been developed, by which it is possible to measure following tissue perfusion parameters: blood flow (BF), circulating blood volume (BV), mean transit time (MTT) and vascular permeability (PS or K trans). Results obtained by different CT perfusion software are not comparable. Standardized perfusion value (SPV) is a universal semi-quantitative indicator of tissue perfusion, which is independent of the CT perfusion algorithm and can be simply calculated in the absence of commercial CT perfusion software. Values of BF, BV and PS are significantly higher, and MTT is shorter in the majority of high-grade malignant tumors compared to low-grade, benign tumors and healthy tissue. Significant decline of CT perfusion parameter values is a marker of good response of neoplasm to the oncological therapy.
Keywords: CT perfusion, imaging, oncology